The importance of complex numbers in mathematics - Buchukhishvili, Mamuli (International Scientific Conference “EDUCATION, RESEARCH, PRACTICE” Proceedings, 2024)
Complex - is a Latin word that means a connection, a combination of things, a set of events or properties. Complex - a concept in psychology is a set of subconscious, mental factors in the consciousness of an individual, which are related to specific subjects or topics and have a significant influence on the behavior of the individual. In mathematics, the term "complex number" is found, and therefore a complex number that is different from the real number. The discovery of complex numbers had a huge impact on all of mathematics, unifying many things that were previously inexplicable. In the article, I will discuss the history of semotan of complex numbers and, based on a specific example, discuss the results related to the solution of cubic equations.